If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -5(3 + x) + -2x = -10x 18 + (3 * -5 + x * -5) + -2x = -10x 18 + (-15 + -5x) + -2x = -10x Combine like terms: 18 + -15 = 3 3 + -5x + -2x = -10x Combine like terms: -5x + -2x = -7x 3 + -7x = -10x Solving 3 + -7x = -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 3 + -7x + 10x = -10x + 10x Combine like terms: -7x + 10x = 3x 3 + 3x = -10x + 10x Combine like terms: -10x + 10x = 0 3 + 3x = 0 Add '-3' to each side of the equation. 3 + -3 + 3x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = 0 + -3 3x = 0 + -3 Combine like terms: 0 + -3 = -3 3x = -3 Divide each side by '3'. x = -1 Simplifying x = -1
| 6x+7+113=180 | | -r=-28 | | 6x+7=113 | | -9.4q+1.1=40.4-1.1 | | 8y+1+6x+7=180 | | 8x-52=108-2x | | 3+c=-12-3c | | (10-8i)(2-3i)=0 | | 27=m^3 | | x+x-28=180 | | 27=m | | In(x+3)-4=In(x-5) | | 5x+11-25x= | | x-3(x+2)=8 | | x-40=180 | | 2n-13=n+8 | | 9+11n=4 | | x+14=3x-26 | | 60-4x=-7x-27 | | Uk+uz=t | | (x+4y)(y+4x)=16 | | n^2-6n+3=2(3n-16) | | 2b^2+9=0 | | 20.6=(180+x)180 | | (3x^2-4xy^2)dx+(x^3-4x^2+12y^3)dy=0 | | 5x+5y=-21 | | 25x+10y+5z=55 | | 27h^3=216 | | 8x+6-20x= | | 16x+7=17x-1 | | 6(2+4)=4(3x+6) | | -7(x+1)-16=30+3 |